2018
DOI: 10.1177/0963689718805375
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from IDO1-Overexpressing Rat Bone Marrow Mesenchymal Stem Cells Promote Immunotolerance of Cardiac Allografts

Abstract: Background:The immunosuppressive activity of mesenchymal stem cells (MSCs) has been exploited to induce tolerance after organ transplantation. The indoleamine 2,3-dioxygenase (IDO) may have beneficial effects in the immunoregulatory properties of MSCs. It was recently revealed that exosomes derived from MSCs play important roles in mediating the biological functions of MSCs. This study aimed to explore the roles of exosomes derived from MSCs in the induction of immune tolerance.Methods:Dendritic cells (DCs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 54 publications
1
45
0
Order By: Relevance
“…A large number of experimental and clinical studies demonstrated beneficial effects of MSC-Exos in the suppression of autoimmune and chronic inflammatory eye diseases [88][89][90][91][92][93][94][95]. Intravenous as well as periocular administration of MSC-Exos efficiently attenuated experimental autoimmune uveitis (EAU) [89,90].…”
Section: Msc-ev-based Attenuation Of Autoimmune and Inflammatory Eyementioning
confidence: 99%
See 1 more Smart Citation
“…A large number of experimental and clinical studies demonstrated beneficial effects of MSC-Exos in the suppression of autoimmune and chronic inflammatory eye diseases [88][89][90][91][92][93][94][95]. Intravenous as well as periocular administration of MSC-Exos efficiently attenuated experimental autoimmune uveitis (EAU) [89,90].…”
Section: Msc-ev-based Attenuation Of Autoimmune and Inflammatory Eyementioning
confidence: 99%
“…MSC-Exos contain a growth related oncogene (GRO), which suppresses production of Th17-inducing cytokines (IL-1β, IL-6 and IL-23) in DCs and prevent Th17 cell-driven inflammation [91,92]. In addition to GRO, MSC-sourced Indoleamine 2-3 dioxygenase (IDO) was responsible for MSC-Exo-based suppression of DC-dependent generation of Th17 cells [93,94]. Exos obtained from IDO-overexpressing MSCs down-regulated expression of co-stimulatory molecules and suppressed production of Th17-inducing cytokines in DCs, attenuating their capacity for activation of naïve T cells and generation of inflammatory Th17 cells [93,94].…”
Section: Msc-ev-based Attenuation Of Autoimmune and Inflammatory Eyementioning
confidence: 99%
“…These biomolecules can be divided into the following categories, and have protective functions in different tissues: (1) angiogenesis factors, such as vascular endothelial growth factor (VEGF), insulin-like growth factor (IGF-1), and hepatocyte growth factor (HGF); (2) anti-apoptotic factors, such as basic fibroblast growth factor (bFGF), transforming growth factor (TGF), and granulocyte macrophage-colony stimulating factor (GM-CSF); (3) anti-inflammatory factors, such as TNF-a-stimulated gene/protein (TSG), interleukin (IL-10), and heme oxygenase (HO) [41,42]. Additionally, soluble factors such as immunoregulatory protein produced by cells can be found to be sealed in vesicles [43]. These secretomes can mediate diverse functions via a cross-talk between different cell types, and are easily affected by organism environment in vivo [44][45][46].…”
Section: Characterization Of Mscs and Their Secretomesmentioning
confidence: 99%
“…Bartosh et al [58] observed that the secretion of anti-inflammatory molecules, namely TNF-α-stimulated gene-6 (TSG-6) and STC-1, by MSCs was increased after three-dimensional spheroid culturing, which decreased inflammation in vivo and macrophage activation in vitro. In addition, TGF-β and interferon-γ (IFN-γ) stimulation [30], the overexpression of angiopoietin-1 [59], HO-1 or other genes [43], and neutralizing antibodies can also change the secretory composition of MSCs and affect their functions.…”
Section: Msc-derived CMmentioning
confidence: 99%
See 1 more Smart Citation